Pengaruh Hedonisme dan Religiusitas Terhadap Perilaku Konsumtif Mahasiswa - Arif Rahmat; Asyari Asyari; Hesi Eka Puteri (EKONOMIKA SYARIAH : Journal of Economic Studies, 2020)
This study aims to analyze the influence of hedonism and religiosity on the consumptive behavior of students at the Faculty of Islamic Economics and Business, State Islamic Institute of Bukittinggi, West Sumatera, Indonesia. The population in this studi was 3,900 students and the sample was 363 of them that were selected by using the cluster sampling techniques. The results showed that hedonism has a positive influence on the consumptive behavior of students, it means that the higher of the level of hedonism, the higher the consumptive behavior of students. Meanwhile, religiosity was found to have the negative effect on the consumptive behavior of students, its meant that  the higher the level of religious students, the lower the consumptive behavior of students, this study suggests that hedonism and religiosity explain variations in student consumer behavior by 64.5%, while the remaining 35.5% % is explained by other variables not explored in this study. This finding shows that to manage consumption properly, students must control their hedonism and increase their level of religiosity so that they will far from consumptive habits.